DIFFERENT METHODS OF TEACHING GRAMMAR - Hasanova Dilshoda (TADQIQOTLAR.UZ, 2024)
Abstract. As a teacher, either of English as a second language or foreign language, it is very important to know different approaches to effective instruction in the English language classroom. When it comes to teaching grammar, for example, deductive and inductive approaches are two commonly used methods by many teachers. For the sake of understanding, this post is about the inductive approach. It will provide examples, benefits, and steps to teach grammar inductively. The inductive approach in teaching grammar is a discovery learning approach in which teachers don’t teach the grammatical rules directly but let students discover them through a learning experience in terms of using the target language.